Karakterisasi kandungan vitamin B12, folat dan isoflavon tempe kedelai dengan isolat murni Rhizopus oryzae, Rhizopus oligosporus, dan Rhizopus stolonifer sebagai bahan pangan fungsional - Vira Putri Yarlina; Dea Indriani Astuti (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
Tempeh is a fermented food ingredient from soybeans that uses various Rhizopus molds, such as Rhizopus oligosporus, Rhizopus oryzae, Rhizophus stolonifer. In this study, the preparation of tempe using mixed culture was carried out in the ratio of Rhizopus oryzae, Rhizopus oligosporus, Rhizopus stolonifer inoculums, namely 1: 1: 1; 1: 2: 1; 2: 1: 2; 1: 1: 2; 2: 1: 1; market yeast